2013
DOI: 10.1055/s-0033-1347247
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Fasting during Ramadan on the Glycemic Control of Patients with Type 2 Diabetes Mellitus

Abstract: In this study, we concluded that fasting during Ramadan did not worsen the glycemic control of patients with type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
2
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 3 publications
6
30
2
4
Order By: Relevance
“…However, the results of this study did not support our hypothesis. While we failed to find comparable studies of fasting effects in schizophrenia patients, our results were in contrast with studies that reported beneficial effects of fasting Ramadan on metabolic and inflammatory status in healthy subjects (Attarzadeh Hosseini and Hejazi, 2013;Faris et al, 2012;Lamine et al, 2006) and in patients with diabetes or metabolic syndrome (Karatoprak et al, 2013;Sahin et al, 2013;Shariatpanahi et al, 2008). Instead, we could not demonstrate in the schizophrenia patients any benefits from fasting during Ramadan in terms of the parameters studied, but we found that, especially if these patients had additionally metabolic syndrome, fasting was associated with a reduction of the useful HDL-c and BDNF levels and elevation of measurements of glucose, insulin, insulin resistance (HOMA-IR), TC, TG, LDL-c, WBCs, granulocytes, lymphocytes, monocytes, fibrinogen, BDNF and hs-CRP, as well as increased systolic and diastolic blood pressure and PANSS total and subscale scores.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the results of this study did not support our hypothesis. While we failed to find comparable studies of fasting effects in schizophrenia patients, our results were in contrast with studies that reported beneficial effects of fasting Ramadan on metabolic and inflammatory status in healthy subjects (Attarzadeh Hosseini and Hejazi, 2013;Faris et al, 2012;Lamine et al, 2006) and in patients with diabetes or metabolic syndrome (Karatoprak et al, 2013;Sahin et al, 2013;Shariatpanahi et al, 2008). Instead, we could not demonstrate in the schizophrenia patients any benefits from fasting during Ramadan in terms of the parameters studied, but we found that, especially if these patients had additionally metabolic syndrome, fasting was associated with a reduction of the useful HDL-c and BDNF levels and elevation of measurements of glucose, insulin, insulin resistance (HOMA-IR), TC, TG, LDL-c, WBCs, granulocytes, lymphocytes, monocytes, fibrinogen, BDNF and hs-CRP, as well as increased systolic and diastolic blood pressure and PANSS total and subscale scores.…”
Section: Discussioncontrasting
confidence: 99%
“…(39) However, other studies have shown that insulin sensitivity improved in men with the metabolic syndrome who fast during Ramadan. (40, 41) Routine periodic fasting (fasting for 24 hours once a month) in a primarily Caucasian population was associated with a lower prevalence of diabetes. (42) It is possible that differences in duration and frequency of fasting differentially impact diabetes risk and understanding what aspects of fasting impact diabetes risk will be important.…”
Section: Discussionmentioning
confidence: 99%
“…Perk et al ( 25 ) found that blood pressure control in patients on medications for HTN was not affected by fasting in Ramadan. Sahin et al studied 122 patients with type 2 DM who fasted during Ramadan and showed that Ramadan fast did not interfere with control of blood glucose in these patients ( 26 ) and according to the Benaji et al ( 21 ), patients with DM, who are alert, correctly treated, and monitored closely, can fast without worsening their medical condition. Although our patients with HTN or DM (controlled with oral agents) were able to fast safely during Ramadan, we would suggest more investigations to determine whether Ramadan fast is safe in these subgroups of patients.…”
Section: Discussionmentioning
confidence: 99%